PERCEPÇÕES DE PROFISSIONAIS DA EQUIPE MULTIDISCIPLINAR DE SAÚDE EM RELAÇÃO ÀS ATIVIDADES LÚDICAS EM HOSPITAIS PÚBLICOS PEDIÁTRICOS DE SÃO LUÍS DO MARANHÃO - LIMA, Antônio José Araújo (2017)
Child hospitalization is a difficult process for the child's development in a hostile and indifferent environment with resistance to adapt to the new reality. The playful care helps to make the stay in the hospital easier, favors the child's development and healing. The feeling of finitude of life afflicts the child, the family those who accompany him in the hospital, during hospitalization. The imminent fear of death, the homesickness of the home makes difficult the relationship with: nurses, doctors, psychologists, physiotherapists, among others. In the context, we investigated the perceptions of professionals of the multidisciplinary health team in relation to the development of play activities in 2 pediatric public hospitals of São Luís/MA. An exploratory, descriptive research was developed. The participants were 8 professionals belonging to the health area, among them, 2 are doctors, 2 nurses, 2 psychologists and 2 occupational therapists, 6 of which are female and 2 are male, with an average of 6 years of professional experience in hospitals. The data were collected through semi-structured interviews. The results indicate that play activities developed with children are relevant in the processes of socialization and integration of the child to the reality of hospitalization. The professionals of the multidisciplinary health team emphasize that the play activities developed in pediatric hospitals contribute to the recovery process of the child's health, adding to the treatment of the pathology.